Buyer-seller watermarking protocols with off-line trusted third parties. (10th December 2008) - Fan, Chun-I; Chen, Ming-Te; Sun, Wei-Zhe
In a buyer-seller watermarking protocol, buyers and sellers protect the ownerships or copyrights of their digital contents through the watermarks embedded in them. However, some known attacks and problems are still threatening the security of the watermarking mechanisms so far. Although several solutions have been introduced in the literature, none can cope with all problems. In this paper, we propose a novel buyer-seller watermarking protocol, with an off-line trusted third party, that can withstand the attacks and resolve the dispute between the buyers and the sellers fairly. Furthermore, our proposed protocol can guarantee the anonymity of the buyers as well.